The power of C++ - Ehman, Ashley (New York Cavendish Square, 2018)
This book introduces readers to important concepts like object-oriented programming while elaborating on the history of the C++ computer programming language, provides examples of code, and explores the relationship between C++, C, and C#. Full-color photographs, a glossary, an index, and sidebars are also included.--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: C++ (Computer program language)